Efektivitas Penerapan Teknik Behavioral Contract Melalui Bimbingan Kelompok untuk Mereduksi Kecanduan Game Online Siswa - Stefanus Lio; Yohanes Natalius Kefi; Dhiu Margaretha; Rosa Mustika Bulor (Jurnal Studia Insania, 2022)
This study aimed to determine the effectiveness of applying the behavioral contract technique through group guidance to reduce online game addiction among students. The method used in this research was descriptive quantitative with a one-group pretest-posttest design. The subjects of this study were six students in class XI IPS 2 at St. Carolus Catholic High School. The instruments used in this study were an online game addiction questionnaire and behavioral contract intervention guidelines. Data analysis was performed using a paired samples t-test. The results of the analysis showed that the t-value was 13.727, while the t-table value at the 5% significance level was 2.776. Thus, t-value was greater than the t-table, indicating that the behavioral contract technique through group guidance was effective in reducing online game addiction in class XI IPS 2 students at St. Carolus Catholic High School in the 2022/2023 academic year.